Open-label trial of anterior limb of internal capsule–nucleus accumbens deep brain stimulation for obsessive-compulsive disorder: insights gained. Issue 7 (15th February 2019) - Huys, Daniel; Kohl, Sina; Baldermann, Juan Carlos; Timmermann, Lars; Sturm, Volker; Visser-Vandewalle, Veerle; Kuhn, Jens
Abstract : Background: For more than 15 years, deep brain stimulation (DBS) has served as a last-resort treatment for severe treatment-resistant obsessive-compulsive disorder (OCD). Methods: From 2010 to 2016, 20 patients with OCD (10 men/10 women) were included in a single-centre trial with a naturalistic open-label design over 1 year to evaluate the effects of DBS in the anterior limb of the internal capsule and nucleus accumbens region (ALIC-NAcc) on OCD symptoms, executive functions, and personality traits. Results: ALIC-NAcc-DBS significantly decreased OCD symptoms (mean Yale-Brown Obsessive Compulsive Scale reduction 33%, 40% full responders) and improves global functioning without loss of efficacy over 1 year. No significant changes were found in depressive or anxiety symptoms. Our study did not show any effect of ALIC-NAcc-DBS on personality traits or executive functions, and no potential outcome predictors were identified in a post hoc analysis. Other than several individual minor adverse events, ALIC-NAcc-DBS has been shown to be safe, but 35% of patients reported a sudden increase in anxiety and anhedonia after acute cessation of stimulation. Conclusions: We conclude that ALIC-NAcc-DBS is a well-tolerated and promising last-resort treatment option for OCD. The cause of variability in the outcome remains unclear, and the aspect of reversibility must be examined critically. The present data from one of the largest samples of patients with OCD treated with DBS thus far support the results of previous studies with smaller samples.